Functional screening of beneficial strains and consortia to maximize healthy fermentation potential - Özturk, Zeynep (My University, 2023)
Legumes and cereals are globally consumed plant-based sources known for their health benefits, including low-fat and high protein content. However, they also contain antinutritional elements. This thesis, conducted as part of the EU Horizon project "Healthferm," aimed to screen food fermentation lactic acid bacteria for optimal fermentation and health-promoting effects. In this study, oat flour (OatF-F), oat protein concentrate (OatF-C) and faba bean protein concentrate (Faba-C) based media were used. Overall, the strains demonstrated good bacterial growth in all media, notably, Faba-C supported favorable growth. Additionally, the impact of overnight incubation without shaking on strain growth was examined. The study found that the growth rate was higher in OatF-F. Moreover, the growth rate of strains in media not incubated overnight with shaking was generally higher. Reductions in pH were observed with selected strains in all media. In the scale-up fermentation, the lowest pH values after 24 hours were observed in OatF-F (3.5±0.02), OatF-C (3.4±0.03), and Faba-C (4.4±0.03). Rhamnose was not detectable in any of the samples, and raffinose was not detected in Faba-C. Complete degradation of raffinose was achieved in OatF-C. Complete hydrolysis of sucrose was observed in Faba-C. Faba-C exhibited a higher concentration of glucose (1.49 g/L), but complete hydrolysis was observed.
Keywords: Plant-based, sustainable, fermentation, screening, lactic acid bacteria, legume, cereal